Methods of Counselling in People with Drug Dependence: A Scoping Review (Indonesian Contemporary Nursing Journal (ICON Journal), 2023)
Aims: Drugs today are one of the urgent and complex problems. One of the interventions that can be done to motivate quitting drug addiction is counselling This study aims to map evidence related to the strategies of counselling in victims of drug abuse and strategies in conducting counselling.Methods: Search databases for this study were PubMed, CINAHL, Science Direct and Google Scholar. Article identification was carried out based on the criteria for the year of publication (2013-2022), RCT / A Cross Section Study/Cross-Sectional Study, English and Indonesian Language, Fulltext, Teenagers to the elderly. Using the PRISMA flowchart, data extraction and scoping with the keywords (English): “Drug Dependence OR Subtance Abuse AND Counselling AND Drug Abuser” and keywords in Indonesian language “Ketergantungan Narkoba OR Penyalahgunaan Zat AND Konseling AND Pengguna Narkoba”.Results: The results of the study found that of the 9 articles that met the criteria. The main findings reveal that there are strategies in counselling, namely by means of drug counselling (drug handling controlled and monitored by doctors and nurses as psychoeducation providers) and telephone. counselling that can be used in screening and planning action.Conclusion: The conclusion of this study is that in counselling drug users there are several types, methods, and approaches included in the provision of counselling that are more effective in increasing motivation to recover or drug dependence in patients who are prescribed drugs by doctors compared to those who do not have prescription drugs. It is expected to contribute to the field of nursing as a strategy in counselling victims of drug abuse or people with drug addiction.
Keywords: Drug Dependence; Counselling; Drug Abuser.